Characterization of the adaptive cellular and humoral immune responses to persistent colonization of Brucella abortus strain RB51 in a Jersey cow - Boggiatto, Paola M.; Sterle, Haley; Falkenberg, Shollie; Sarlo-Davila, Kaitlyn; Putz, Ellie J.; Olsen, Steven C. (Frontiers in Veterinary Science, 2024)
Brucella abortus strain RB51 is the commercial cattle vaccine used in the United States and many parts of the world against bovine brucellosis. RB51 was licensed for use in 1996, and it has been shown to be safe and efficacious in cattle, eliciting humoral and cellular responses in calves and adult animals. In 2017, an epidemiological trace back investigation performed by the Centers for Disease Control and Prevention (CDC) identified human cases of brucellosis caused by infection with RB51. These infections resulted from the consumption of unpasteurized dairy products, which were traced back to otherwise healthy animals that were shedding RB51 in their milk. At the current time, six adult Jersey cows have been identified in the U.S. that were shedding RB51 in milk. One of the RB51 shedding cattle was obtained and housed at the National Animal Disease Center (NADC) for further study. Improved understanding of host cellular and humoral immune responses to RB51 in persistently colonized cattle may be achieved by characterization of responses in shedding animals. We hypothesized, based on the lack of RB51 clearance, that the RB51-shedder animal has a diminished adaptive cellular immune response to RB51. Our data demonstrate that in the presence of persistent RB51 infection, there is a lack of peripheral anti-RB51 CD4+ T cell responses and a concurrent high anti-RB51 IgG humoral response. By understanding the mechanisms that result in RB51 persistence, development of improved intervention or vaccination for brucellosis may be facilitated that would provide public health benefits including reducing risks associated with consumption of non-pasteurized milk products.